MAGICAL REALISM IN ANIME: THE TUNNEL TO SUMMER, THE EXIT OF GOODBYES (2022) - Ahsan, Afwa Izzul (Universitas Negeri Surabaya, 2026)
This study uses a qualitative analysis of magical realism in the anime “The Tunnel to Summer, the Exit of Goodbyes” (2022), with the main goal of identifying the elements of magical realism as depicted in the anime and exploring how these elements shape the overall narrative structure. Using a descriptive qualitative method, this study uses Wendy B. Faris’ theory of the five characteristics of Magical Realism to analyze key scenes and dialogues. The analysis confirms the presence of all five characteristics, identifying the Urashima Tunnel as the main “irreducible element,” a magical event set in the “phenomenal world” of Kouzaki City, Japan. “Unsettling doubt” is formed through the absence of any logical or historical explanation for the tunnel’s existence, while “the merging of nature” is demonstrated when the protagonist, Tono, brings his dead parakeet back to the real world alive and physically enters scenes from his past. Finally, the anime features “disruptions of time, space, and identity” through measurable time shifts, the tunnel’s ability to manifest psychological memories as physical space, and Tono’s past and present selves coexisting. The study concludes that these elements fundamentally disrupt the anime’s narrative structure. The narrative does not employ traditional conflict, instead focusing on the characters’ hesitations in using the tunnel.